Differences between transient neonatal diabetes mellitus subtypes can guide diagnosis and therapy. Issue 4 (April 2021) - Bonfanti, Riccardo; Iafusco, Dario; Rabbone, Ivana; Diedenhofen, Giacomo; Bizzarri, Carla; Patera, Patrizia Ippolita; Reinstadler, Petra; Costantino, Francesco; Calcaterra, Valeria; Iughetti, Lorenzo; Savastio, Silvia; Favia, Anna; et al.
Abstract : Objective: Transient neonatal diabetes mellitus (TNDM) is caused by activating mutations in ABCC8 and KCNJ11 genes (KATP /TNDM) or by chromosome 6q24 abnormalities (6q24/TNDM). We wanted to assess whether these different genetic aetiologies result in distinct clinical features. Design: Retrospective analysis of the Italian data set of patients with TNDM. Methods: Clinical features and treatment of 22 KATP /TNDM patients and 12 6q24/TNDM patients were compared. Results: Fourteen KATP /TNDM probands had a carrier parent with abnormal glucose values, four patients with 6q24 showed macroglossia and/or umbilical hernia. Median age at diabetes onset and birth weight were lower in patients with 6q24 (1 week; −2.27 SD) than those with KATP mutations (4.0 weeks; −1.04 SD) ( P  = 0.009 and P  = 0.007, respectively). Median time to remission was longer in KATP /TNDM than 6q24/TNDM (21.5 weeks vs 12 weeks) ( P  = 0.002). Two KATP /TNDM patients entered diabetes remission without pharmacological therapy. A proband with the ABCC8 /L225P variant previously associated with permanent neonatal diabetes entered 7-year long remission after 1 year of sulfonylurea therapy. Seven diabetic individuals with KATP mutations were successfully treated with sulfonylurea monotherapy; four cases with relapsing 6q24/TNDM were treated with insulin, metformin or combination therapy. Conclusions: If TNDM is suspected, KATP genes should be analyzed first with the exception of patients with macroglossia and/or umbilical hernia. Remission of diabetes without pharmacological therapy should not preclude genetic analysis. Early treatment with sulfonylurea may induce long-lasting remission of diabetes in patients with KATP mutations associated with PNDM. Adult patients carrying KATP /TNDM mutations respond favourably to sulfonylurea monotherapy.